How democratic is higher education for sustainable development?. Issue 5 (3rd September 2017) - Shephard, Kerry; Brown, Kim
ABSTRACT: We wondered how 'democracy' was being used and communicated within the higher education discourse of 'education for sustainability', or 'for sustainable development' (ES/ESD). We used a philosophical hermeneutic approach to explore the sense or senses in which the concept of democracy is used within this literature and supported our analysis by incorporating text about democracy from other disciplines. We conclude from our analysis that the concept of democracy within ES/ESD texts has evolved to suggest many meanings that in their entirety do not support our shared research mission towards ES/ESD. At the pens of ES/ESD scholars, democracy may have become one of Sartori's intolerably blunted conceptual tools.